BIO-ENGINEERING, MELALUI PEMANFAATAN TANAMAN KALIANDRA (CALIANDRA CALOTHYRSUS) DI WILAYAH ZONA RAWAN LONGSOR JAWA BARAT - -, Zufialdi Zakaria; -, Dicky Muslim; -, Raden Irvan Sophian; -, Sondi Kuswaryan; -, Ujang Hidayat Tanuwiria (Bulletin of Scientific Contribution, 2013)
Landslides prone areas can be occur due to a large slope, open slopes, large erosion rate, or a large infiltration. Landslide prone areas can be prevented by a stable slope engineering. Engineering of stable slopes can be integrated through a variety of methods with preliminary procedure : 1) Mapping of landslides prone areas, 2) Slope stability analysis through the study of Safety Factor, 3) Engineering of slope stabilization and integrated through the simulation stable slope, slope design and other engineering, 4) Environmental management and environmental monitoring, 5) Bio-engineering by utilizing plants as part of a stable slope engineering systems, namely as a preventive agent of erosion, reduction of infiltration and runoff flow, landslide prevention as well as strengthening the slopes . Engineering can use the model of Starlet (Stabilisati dan Rancangbangun Lereng Terpadu, or Engineering of Slope Stabilization and Integrated) involving the role of government officials, industrial and businessmen , residents / communities , and scientists . Kaliandra chosen to be a plant that is part of a stable slope engineering . Kaliandra plants have a good root, the tree canopy is not heavy, high-protein leaves for fodder, stems and twigs are dried for energy (fuelwood ) . These plants, in addition to prevention of landslides, will be useful for people and industry.